Kesejahteraan Guru Bahasa Inggris Bersertifikat dan Pengaruhnya Terhadap Kualitas Pembelajaran di Kelas di Banjarbaru - Listia, Rina; Elyani, Eka Puteri (English Education:Journal of English Teaching and Research, 2022)
Teachers’ involvement in the process of education has a significant influence on the quality of educational outcomes.Teachers' performance in the teaching and learning process are expected to improve as teachers' welfare is improved. Improving teachers' welfare can then have a positive impact on improving teacher quality conceptually and in practice. As a result, teachers’ certification comes as the new spirit given from the government to improve teachers’ performance in the classroom. This study aims at investigating the impact of teachers' welfare enhancementon their learning performance in the classroom. This study employs descriptive qualitative research that describes the effect of teachers’ certification allowances on the improvement of teaching and learning quality in the classroom. The participants of this study are 30 teachers from the representative of MGMP teachers in Banjarbaru who have accepted teacher professional allowance. Moreover, questionnaire, interview, and observation are taken to collect the data.According to the findings, all certified teachers at the junior high, senior high, and vocational high school levels have already understood the meaning of pedagogical and professional competence that they use to deliver the material in the classroom; in general, teachers have well prepared the material. Teachers use teaching materials that are relevant to the syllabus and students' needs, allowing them to teach in accordance with Graduate Competency Standards (SKL). Certified English teachers also have already mastered the theories and principles of effective learning that are being taught in the classroom. In a nutshell, there is a correlation between certified English teachers' welfare and the improvement of classroom learning quality.